Spatial modeling of land resources and constraints to guide urban development in Saudi Arabia’s NEOM region using geomatics techniques - Alogayell, Haya M.; Kamal, Ahmed; Alkadi, Ibtesam I.; Ramadan, Mona S.; Ramadan, Rasha H.; Zeidan, Ali M. (Frontiers in Sustainable Cities, 2024)
This research presents a GIS-based approach to evaluate land suitability for the urbanization of Saudi Arabia's NEOM region, an ambitious initiative for sustainable development within a desert setting. By employing a multi-criteria decision-making framework, we have synthesized data on land resources, stability, accessibility, construction costs, and proximity to conservation areas using the Analytical Hierarchy Process (AHP) to prioritize these factors based on their importance for sustainable growth.Our analysis reveals that areas designated with grid values of 9 and 8, totaling 6312.33 square kilometers or 28.23% of the area studied, are most favorable for urban development. These sectors span the northern, central, and southern parts of NEOM, notable for their strategic location near future infrastructure and natural assets conducive to sustainable practices. This finding supports NEOM's key initiatives like "The Line," "Oxagon," and "TROJENA," showcasing the model's utility in directing urban development strategies.The paper discusses the broader socioeconomic and environmental ramifications of pinpointing areas suited and unsuited for development, underlining the model's role in facilitating decision-making that aligns urban expansion with environmental stewardship. Furthermore, it advocates for leveraging development-restricted zones in conservation efforts and renewable energy ventures.Nevertheless, the study concedes certain limitations, such as the dependence on static datasets and inherent challenges related to the AHP method, including the presumption of criteria independence. Future research avenues are proposed, emphasizing the integration of dynamic data sources, comprehensive socio-cultural impact evaluations, and the adoption of flexible urban planning methodologies to refine the model's precision and practicality. Overall, this detailed examination showcases NEOM's blueprint as an exemplar for future urban environments, illustrating a systematic strategy for developing desert regions that integrate innovation, ecological sustainability, and the preservation of cultural heritage.